Prevalence of and risk factors for anal high-risk HPV among HIV-negative and HIV-positive MSM and transgender women in three countries at South-East Asia. Issue 10 (March 2018) - Somia, I Ketut Agus; Teeratakulpisarn, Nipat; Jeo, Wifanto S.; Yee, Ilias A.; Pankam, Tippawan; Nonenoy, Siriporn; Trachuntong, Deondara; Mingkwanrungrueng, Pravit; Sukmawati, Made Dewi D.; Ramautarsing, Reshmie; Nilasari, Hanny; Hairunisa, Nany; et al.
Abstract : Abstract: This study aimed to assess the prevalence of and associated risk factors for anal high-risk human papillomavirus (hr-HPV) infection among men who have sex with men (MSM) and transgender women (TGW) in Indonesia, Thailand, and Malaysia. This was baseline data from a prospective cohort study with clinic sites in Jakarta and Bali (Indonesia), Bangkok (Thailand), and Kuala Lumpur (Malaysia). MSM and TGW aged 18 years and older from Indonesia, Thailand, and Malaysia were enrolled. Demographic and behavioral characteristics were assessed, and anal samples were collected for HPV genotyping. Multivariate logistic regression models were used to assess risk factors for anal hr-HPV overall and among HIV-positive participants. A total of 392 participants were enrolled, and 48 were TGW. As many as 245 were HIV-positive, and 78.0% of the participants were on combination antiretroviral therapy (cART). Median CD4 count was 439 cells/mm 3 and 68.2% had undetectable HIV-RNA. HIV-positive participants had significantly more hr-HPV compared to HIV-negative participants (76.6% vs 53.5%, P < .001). HPV-16 was the most common high-risk type (20%), whereas HPV-33, -39, and -58 were significantly more common among HIV-positive participants. HIV-positive participant significantly associated with anal hr-HPV infection compared with HIV-negative (OR: 2.87, 95% CI: 1.76–4.70, P ⩽ .001), whereas among HIV-positive participants transgender identity had lower prevalence of hr-HPV infection (OR: 0.42, 95% CI: 0.19–0.91, P = .03). High-risk HPV infection was very common among MSM and TGW in South-East Asia. Overall, HIV-infection, regardless of cART use and immune status, significantly increased the risk, while among HIV-positive participants transgender identity seemed to decrease the risk of anal hr-HPV. Abstract : Supplemental Digital Content is available in the text